A Simulation Model for the Attention to Users in Emergency Situations in the City of Bogotá (2018)
A simulation model is presented for the attention to users in emergency situations in Bogota. This system is vital importance for the development, security and stability of the city. The simulation process begins with an intelligence model that allows acquiring the knowledge of complex process of attention of users and understanding relationships among resources which attend emergencies. This system is managed by Emergency Regulatory Center (ERC) assigned to the District Health Secretary. Within the results achieved, it is possible to obtain an improvement in measures of performance such as average time in the system and the average time blocked which show an inadequate level service because they are result of excessive time in waiting calls and the subsequent system exit. Different scenarios were proposed in order to increase reception capacity of the incidents in the activation system’s phase, which is equivalent to increase the technicians auxiliaries of regulatory medical (TARM) and of the regulatory doctor (RD). © 2018, Springer Nature Switzerland AG.